AB1055 CERTOLIZUMAB PEGOL: A SAFE AND EFFICIENT TREATMENT IN PATIENTS WITH UVEITIS DURING PREGNANCY. (2nd June 2020) - Prieto-Peña, D.; Calderón-Goercke, M.; Adan, A.; Chamorro-López, L.; Maiz, O.; De Dios-Jiménez Aberásturi, J.; Veroz Gonzalez, R.; Blanco, S.; Santos, J. M.; Navarro, F.; Gallego, A.; González-Suárez, S.; et al.
Abstract : Background: Anti-TNFα agents are useful in uveitis (1-5). Certolizumab pegol (CZP) differs from other anti-TNFα agents due to its limited placental transfer. Objectives: To assess efficacy and safety of CZP in women with uveitis during pregnancy. Methods: Multicenter study of women with uveitis under CZP during pregnancy and their neonates. Results: 14 women (23 eyes); mean age 34.3±5.5 yrs (TABLE 1 ). Pattern of uveitis: 10 anterior, 2 posterior, 1 intermediate, 1 panuveitis. Uveitis was bilateral in 9 and chronic in 7. CZP was started before conception in 10 patients and after in 4. All patients obtained or maintained ocular remission throughout pregnancy (FIGURE ). Prednisone was reduced from a mean dose of 21.7±19.7 mg/day to 4.1±3.8 mg/day at 6 months (p=0.03), leading to complete discontinuation in 4. 15 healthy infants were born. Only 1 woman presented a mild infection. No infections or malformations were found in neonates after a follow-up of 6 months. 6 infants were breastfed and all received scheduled vaccinations without complications (TABLE 2). Conclusion: CZP seems to be effective and safe in female patients with uveitis during pregnancy and neonates. References: [1]Llorenç V et al. Certolizumab Pegol, a New Anti-TNF-α in the Armamentarium against Ocular Inflammation. Ocul Immunol Inflamm. 2016;24(2):167-72. doi: 10.3109/09273948.2014.967779 [2]Urruticoechea-Arana A et al. Efficacy and safety of biological therapy compared to synthetic immunomodulatory drugs or placebo in the treatment of Behçet's disease associated uveitis: a systematic review. Rheumatol Int. 2019 Jan;39(1):47-58. doi: 10.1007/s00296-018-4193-z [3]Martín-Varillas JL et al. Successful Optimization of Adalimumab Therapy in Refractory Uveitis Due to Behçet's Disease Ophthalmology. 2018 Sep;125(9):1444-1451. doi: 10.1016/j.ophtha.2018.02.020 [4]Santos-Gómez M et al. The effect of biologic therapy different from infliximab or adalimumab in patients with refractory uveitis due to Behçet's disease: results of a multicentre open-label study. Clin Exp Rheumatol. 2016. Sep-Oct;34(6 Suppl 102): S34-S40 [5]Calvo-Río V et al. Golimumab in refractory uveitis related to spondyloarthritis. Multicenter study of 15 patients.Semin Arthritis Rheum. 2016 Aug;46(1):95-101. doi: 10.1016/j.semarthrit.2016.03.002 Disclosure of Interests: D. Prieto-Peña: None declared, Monica Calderón-Goercke: None declared, Alfredo Adan: None declared, Lillian Chamorro-López: None declared, Olga Maiz: None declared, JR De Dios-Jiménez Aberásturi: None declared, Raul Veroz Gonzalez: None declared, Soledad Blanco: None declared, José M Santos: None declared, Francisco Navarro: None declared, Adela Gallego: None declared, Senen González-Suárez: None declared, Arantxa Conesa: None declared, Andrea García-Valle: None declared, Miguel Cordero-Coma: None declared, Nieves Pardiñas-Barón: None declared, Rosalía Demetrio-Pablo: None declared, Vanesa Calvo-Río Grant/research support from: MSD and Roche, Speakers bureau: AbbVie, Lilly, Celgene, Grünenthal, UCB Pharma, Victor Manuel Mora-Cuesta: None declared, Santos Castañeda: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, Roche, Consultant of: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma and MSD, Speakers bureau: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma. MSD